Management of fungal peritonitis : a Moroccan single peritoneal dialysis unit experience - Moussokoro Hadja Kone; Tarik Bouattar; Ibtissam Fares; Meryem Benbella; Naima Ouzeddoun; Rabia Bayahia; Loubna Benamar (RDPLF, 2019)
Introduction: Fungal peritonitis (PF) in peritoneal dialysis (PD) is a serious infection that involves the functional prognosis of the peritoneum and the patient's vital prognosis. It must benefit from a fast handling but nevertheless not very codified. Each center therefore ensures an individual care of its patients. Materiel and method: The purpose of our study is to describe our 10-year experience through our patients who presented FP. We performed a descriptive retrospective study of FP cases documented in the PD unit. Results: the prevalence of FP was 5,1%, which represent 9 cases. Predominant clinical signs were dialysat turbidity and abdominal pain. FP was primitive for 3 patients. The antifungal therapy used was Fluconazole, which was combined with an increased number of peritoneal exchanges. DP catheter ablation was done for 8 patients with an average delay of 5.5 days. The overall outcome was favorable and 3 patients continued PD. No death or encapsulating peritonitis was a consequence of FP. Discussion and conclusion: FP is an infectious complication in PD. Its' death rate is elevated; dropping-out of PD rate too is elevated. The favorable evolution of our patients that stayed in PD let us think that it may be possible to maintain more patients in PD after FP.